Frank Plumpton Ramsey: A feminist economist? - Soroush Marouzi (Duke University, Center for the History of Political Economy (CHOPE), 2021)
This paper is an attempt to historicize Frank Plumpton Ramsey's Apostle talks delivered from 1923 to 1925 within the social and political context of the time. In his talks, Ramsey discusses socialism, psychoanalysis, and British women's movement. Ramsey's views on these three intellectual movements of his time were inter-connected, and they all contributed to his take on the then policy debates on the role of women in economy. Drawing on some archival materials, biographical facts, and the historiographical literature of the post-war politics of motherhood, this paper shows that the kind of feminism that explains Ramsey's remarks on women the best is the "new feminism" of the 1920s whose demands were not egalitarian in character.
Keywords: B14; B31; B54; I38; J31; J51; 330; Frank P. Ramsey; Politics of Motherhood; Feminism; Psychoanalysis; Socialism